Analisis Sistem Pemberian Gaji Berdasarkan Persentase Produktivitas dan Hasil Analisis Beban Kerja Pada Pegawai Jurusan - Hery Murnawan; Sasongko Aji Wibowo; Febrian Puji Lestari (Jurnal Serambi Engineering, 2024)
Salaries and productivity have an important role in determining the quality of the workforce in an agency. Salary payments can also affect level of work productivity and workload borne. Focus is calculating thesignificant level, effective level, and optimization of the salary system in the Faculty of Engineering. This research aims to analyze the optimal and effective payroll system in the Faculty of Engineering by referring to the level of performance staff. Method is a quantitative method and applies descriptive quantitative research. Stages in data analysis are reducing data, presenting data, descriptive statistical, validity, reliability, spearman rank correlation analysis, calculating the coefficient of determination, and concludingthe results of the data that has been processed. Results can be stated that compensation and incentives have been carried out quite well. It can also be seen in the results of the empirical average, namely 67.16. There is a relationship between the influence of compensation and incentives and positive performance levels which are classified as quite strong. Meanwhile, the results of the Spearman rank correlation analysis are 0.445. This statement of results shows that level performance at Faculty of Engineering has a fairly strong relationship, namely where compensation and incentives influence work specifications.